Nmr fingerprint comparison of cultivated sideritis spp. From Cyprus - Tomou, Ekaterina Michaela; Lytra, Krystalia; Chrysargyris, Antonios; Tzortzakis, Nikos G.; Skaltsa, Helen (My University, 2021)
Medicinal and Aromatic Plants (MAPs) play an essential role in global health systems, since more than 80% of population use natural products in primary healthcare. Given that the global use of herbal medicines is exponentially increasing, as well as many MAPs products are introduced into the market, many cultivation practices are applied to produce high quality and standardized plant raw materials. Thus, the present study focuses on the chemical fingerprints of two cultivated Sideritis species. In Cyprus, Sideritis cypria Post and S. perfoliata L. subsp. perfoliata are widely used in traditional medicine. To date, there is no research work presenting the comparative chemical profiling between the aforesaid species using NMR methods. In this study, 1D and 2D NMR experiments were used to compare the chemical fingerprints of these species originated from conventional cultivation practices. Iridoids (ajugol, monomelittoside, and melittoside) and one flavone (4′-methyl-isoscutellarein 7-O-[6′′′-O-acetyl]-β-D-allosyl(1→2)glucoside) were present in the infusion of S. perfoliata subsp. perfoliata. The phenylethanoid glycoside, acteoside, was detected in both samples. The phytochemical profiles of these cultivated species were similar to those of Sideritis species, indicating the positive impact of cultivation practices in MAPs.
Keywords: Sideritis; NMR fingerprints; Comparison; Cultivation; Cyprus